(untitled) (Rupantaran: A Multidisciplinary Journal, 2024)
Digital resources in education encompass a wide array of technological tools, online platforms, and digital content utilized to facilitate and enhance the learning process. They serve as invaluable supplements to traditional teaching methods, offering dynamic and diverse ways to impart knowledge, encourage engagement, and foster skill development among learners. This systematic review critically examines the influence of socioeconomic factors on access to digital resources for education by analyzing studies published between 2017 and 2024. The inclusion criteria prioritized empirical studies in English-language peer-reviewed journals or reputable conference proceedings, utilizing various research designs. The review involved a thorough search across databases like JSTOR, APA PsycNet, Wiley Online Library, ERIC, and Google Scholar. The study’s analysis identified key themes, highlighting the profound influence of socioeconomic factors on technology access, engagement, and academic outcomes. The recurring theme of the digital divide emphasized disparities in device ownership, internet connectivity, and effective technology utilization. The nuanced exploration of parenting approaches, gender dynamics, and educational contexts added depth to understanding these influences. This study found the necessity for a holistic approach in educational planning, considering socioeconomic, cultural, and educational factors to effectively address challenges and disparities, ultimately fostering equitable access to digital resources in education.